The Maori Electoral Option Campaign: Problems of Measuring 'Success' - Comrie, Margie; Gillies, Annemarie; Day, Mary (Political Science, 2002)

Coming Home? Māori Voting in 1999 - Sullivan, Ann; Margaritis, Dimitri (Proportional representation on trial, 2002)
Keywords: Coalition governments -- New Zealand; Elections -- New Zealand; New Zealand -- Politics and government -- 1996-; New Zealand Parliament -- Elections, 1999; Political campaigns -- New Zealand; Proportional representation -- New Zealand

Proportional representation on trial - Vowles, Jack; Aimer, Peter; Karp, Jeffrey; Banducci, Susan; Miller, Raymond; Sullivan, Ann (1999 New Zealand general election and the fate of MMP, 2002)
Keywords: Coalition governments -- New Zealand; Elections -- New Zealand; New Zealand -- Politics and government -- 1996-; New Zealand Parliament -- Elections, 1999; Political campaigns -- New Zealand; Proportional representation -- New Zealand

Ngā Kāmiti wahine: theorising the politicisation of Māori women in the late nineteenth century - Rangiheuea, Tania (2002)

Re-colonisation and indigenous resistance: neoliberalism in the Pacific - Bargh, Ema Maria (Australian National University, 2002)

He tipua: the life and times of Sir Āpirana Ngata - Walker, Ranginui (Penguin Books, 2002)
Keywords: apirana ngata; biography; history; ngāti porou; politicians; social conditions

Maori sustainable development in the 21st century: The importance of Maori values, strategic planning and information systems - Harmsworth, Garth; Barclay-Kerr, Kim; Reedy, Tamati (He Puna Korero: Journal of Maori & Pacific Development, 2002)
Keywords: autonomy; economic development; governance; rangatiratanga; self-determination

Sport, Tribes, and Technology: The New Zealand All Blacks Haka and the Politics of Identity - Jackson, Steve; Hokowhitu, Brendan (Journal of Sport & Social Issues - J SPORT SOC ISSUES, 2002)
This study examines how global forces are shaping local indigenous cultures with a particular focus on the relationship between global capitalism, new media technologies, and transnational advertising. Concentrating on Mäori culture and identity in Aotearoa/New Zealand, the authors examine a contemporary political debate related to indigenous culture and intellectual property rights. Specifically, the study explores the politics of identity associated with global sports company Adidas and its use of the traditional New Zealand All Blacks haka as part of a global advertising campaign. A key feature of the analysis is the controversy surrounding a lawsuit filed by a Mäori tribe claiming compensation for the commercial use of its culture. Overall, the study highlights the problem of maintaining and protecting cultural spaces where indigenous identities can be constructed and affirmed.
Keywords: cultural appropriation; identity; intellectual property

Letty Brown, Wahine Toa - Harris, Aroha (Shifting Centres: Women and migration in New Zealand history, 2002)
History of Lettty Brown, advocate and member of groups such as the Womens Welfare League during urbanisation 1950s-1906s
Keywords: mana wāhine; urbanisation